Strengthening rock analysis skills through petrology and petrography training for vocational school students majoring in Geology and Mining Engineering, Makassar City - Farida, Meutia; Irfan, Ulva Ria; Maulana, Adi; Sirajuddin, Haerany; Alimuddin, Ilham; Umar, Hamid; Thamrin, Meinarni; ., Sahabuddin; ., Maulana; Ikhwana, Nur; Asfar, Suryawan (Faculty of Engineering UNHAS, 2023)
Over the last 2 decades, the need for the application of geosciences has become increasingly in society, geological natural disasters have made various levels of society aware of the importance of knowledge and understanding of the geological conditions of the Indonesian Archipelago. One of the impacts is the increasing number of vocational schools and universities providing earth education. Therefore, a curriculum that includes